2016
DOI: 10.1515/intag-2015-0075
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the density of the clay-organic complex in soil

Abstract: Soil bulk density was investigated as a function of soil contents of clay and organic matter in arable agricultural soils at a range of locations. The contents of clay and organic matter were used in an algorithmic procedure to calculate the amounts of clay-organic complex in the soils. Values of soil bulk density as a function of soil organic matter content were used to estimate the amount of pore space occupied by unit amount of complex. These estimations show that the effective density of the clay-organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…They found that soil clay had a critical role in the chemical stabilisation of organic matter through clay-organic complexes in the soils. Czyz and Dexter (2016) pointed out the relation between the magnitude of clay-soil Figure 1. The effect of number of passes on penetration resistance at different depths (passing × depth × treatment).…”
Section: Soil Penetration Resistancementioning
confidence: 99%
“…They found that soil clay had a critical role in the chemical stabilisation of organic matter through clay-organic complexes in the soils. Czyz and Dexter (2016) pointed out the relation between the magnitude of clay-soil Figure 1. The effect of number of passes on penetration resistance at different depths (passing × depth × treatment).…”
Section: Soil Penetration Resistancementioning
confidence: 99%
“…The clay-organic complex in soil has been found to have a very small effective mean density of 170±40 kg m -3 (Czyż and Dexter, 2016). This is a smaller density than that of any other component of soil or of the whole soil.…”
Section: Introductionmentioning
confidence: 92%
“…Low to high values of COCC represent an increasing fraction of SOC complexed with clay and increasingly porous soil structure (sensu Dexter et al, 2008;Czyż and Dexter, 2016). Values of COCC refer to the mass fraction of complexable material (i.e., clay and SOC) predicted to be in organo-mineral complexes.…”
Section: Datasetsmentioning
confidence: 99%